The importance of developing healthy personal boundaries of students for building a sustainable work-life balance - Mariya S. Volkova; Anastasiya A. Silivonenko; Liubov V. Fialkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The research deals with the importance of formation of students personal boundaries to build sustainable work-life balance in their future careers. The paper investigates types of personal boundaries and ways of defending them. This goal is achieved by solving the following tasks: learning the main theoretical approaches to describing the concept of students personal boundaries; identifying types and functions of personal boundaries; analyzing violations of personal space; considering ways of defending boundaries. Emphasis is placed on identifying the presence of personal space and the ability to defend social boundaries among students. Students are in the age of their personality development, somewhere between childhood and adulthood, and therefore their psychological state is especially contradictory: the foundations laid down by their parents are fading into the background, and everything left unsaid is replenished through personal ambitions and personal study of the world around them. Often, the wrong parents approach to bringing up children in the past is reflected in the present and can sometimes become the main cause of the violation of personal boundaries, which often has a significant impact on students life and future work. Therefore, the study of the topic of sovereign space among students becomes relevant. The following methods for studying this problem were used: a comprehensive analysis of the theoretical foundations of the topic of personal boundaries and the surveys results, which confirmed the assumption of importance, its deeper coverage and further research. In future, such methods can be useful for implementing a competent approach to raising people with a stable and healthy psyche, which will have a positive impact on their position in a society and ability to work.